Efficacy and safety of cannabidiol for the treatment of canine osteoarthritis: a systematic review and meta-analysis of animal intervention studies - Patikorn, Chanthawat; Nerapusee, Osot; Soontornvipart, Kumpanart; Lawonyawut, Kanta; Musikpodok, Kachapong; Waleethanaphan, Kanisorn; Anantachoti, Puree (Frontiers in Veterinary Science, 2023)
Introduction: Canine osteoarthritis (OA) is a degenerative disease with chronic inflammation of internal and external joint structures in dogs. Cannabis spp. contains cannabidiol (CBD), a substance known for various potential indications, such as pain relief and anti-inflammatory in various types of animals, including dogs with OA. As CBD is increasingly in the spotlight for medical use, we aimed to perform a systematic review and meta-analysis to evaluate the efficacy and safety of CBD in treating canine OA. Methods: We searched PubMed, Embase, Scopus, and CAB Direct for animal intervention studies investigating the effects of CBD for canine OA from database inception until February 28, 2023. Study characteristics and findings were summarized. A risk of bias in the included studies was assessed. Meta-analyses were performed using a random-effects model to estimate the effects of CBD on pain scores (0-10), expressed as mean difference (MD) and 95% confidence interval (95% CI). Certainty of evidence was assessed using GRADE. Results: Five articles were included, which investigated the effects of CBD in 117 dogs with OA. All studies were rated as having a high risk of bias. CBD products varied substantially, i.e., oral full spectrum CBD oil in four studies, and isolated CBD oil and liposomal CBD oil in another study. Treatment duration varied from 4-12 weeks. Meta- analyses of three studies found that, in dogs with OA, treatment with oral full-spectrum CBD oil may reduce pain severity scores (MD; -0.60, 95% CI; -1.51 to 0.31, I2=45.64%, P=0.19) and pain interference scores (MD; -1.52, 95% CI; -3.84 to 0.80, I2=89.59%, P=0.20) but the certainty of evidence was very low. CBD is generally considered safe and well-tolerated in the short-run, with few mild adverse events observed, such as vomiting and asymptomatic increase in alkaline phosphatase level. Conclusion: CBD is considered safe for treating canine OA. CBD may reduce pain scores, but the evidence is very uncertain to conclude its clinical efficacy. High-quality clinical trials are needed to further evaluate the roles of CBD in canine OA.